Expand the following:
i)
![(3x - 4y) {}^{3} (3x - 4y) {}^{3}](https://tex.z-dn.net/?f=%283x+-+4y%29+%7B%7D%5E%7B3%7D+)
ii)
![(x - 5)( x + 6)(x - 3) (x - 5)( x + 6)(x - 3)](https://tex.z-dn.net/?f=%28x+-+5%29%28+x+%2B+6%29%28x+-+3%29)
iii)
![(a - b + c {)}^{2} (a - b + c {)}^{2}](https://tex.z-dn.net/?f=%28a+-+b+%2B+c+%7B%29%7D%5E%7B2%7D+)
Answers
Answered by
1
Answer:
Given,
to find the value of
( 3x - 4y + 5z ) ²
This can be solved using an algebraic identity ie,
(a + b + c)² = a² + b² + c² + 2ab + 2bc + 2ac
( 3x - 4y + 5z ) ² can be written as
(3x + (-4y) + 5z)²
where,
a = 3x
b = -4y
c = 5z
So,
(3x + (-4y) + 5z)²
= (3x)² + (-4y)² + (5z)² + 2(3x)(-4y) + 2(-4y)(5z) + 2(3x)(5z)
= 9x² + 16y² + 25z² - 24xy - 40yz + 30xz
follow me.....❤❤❤❤❤
Answered by
6
Step-by-step explanation:
1.(3x-4y) ^2
=9x^2-12xy-16y^2.
2.
=x^3-2x^2-33x+90.
3.(a-b+c)^2
=a^2+b^2+c^2-2ab+2ac-2bc.
.
Similar questions